Analisis Manajemen Risiko Terhadap Insiden Penyegelan SMA Negeri 5 Bukittinggi: Tantangan Sistem PPDB dan Dampaknya pada Kelangsungan Belajar Mengajar - Fadilul Rahman; Julia Salsabila; Hafiz Muhammad Akbar; Indhira Syahputri (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
The implementation of the New Student Admission System (PPDB) based on zoning is intended to ensure equitable access to education. However, in practice, this policy has generated various social and administrative conflicts. One prominent case is the sealing of SMA Negeri 5 Bukittinggi in 2023, which disrupted the teaching and learning process. This study aims to analyze the failure of risk management in the implementation of the PPDB zoning system and its impact on institutional stability and learning continuity. This research employs a literature review method by examining national and international journal articles, education policy documents, and relevant research reports published between 2019 and 2024. Data analysis was conducted through content analysis using the ISO 31000 risk management framework. The results indicate that the absence of systematic risk identification, weak policy communication, and the lack of early warning mechanisms contributed significantly to the escalation of social conflict. The study concludes that integrating risk-based governance into PPDB planning and implementation is essential to prevent similar incidents and to ensure the sustainability of teaching and learning activities in public schools.